The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3348/jksr.2017.76.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interobserver Reproducibility of Shear Wave Elastography for Evaluation of the Breast Lesions

Abstract: Purpose: To evaluate reproducibility of shear wave elastography (SWE) for breast lesions within and between observers and compare the reproducibility of SWE features. Materials and Methods: For intraobserver reproducibility, 225 masses with 208 patients were included; and two consecutive SWE images were acquired by each observer. For interobserver reproducibility, SWE images of the same mass were obtained by another observer before surgery in 40 patients. Intraclass correlation coefficients (ICC) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…In addition, high reproducibility and accuracy in the phantom may not be in accordance with human subjects, which have heterogeneous background surrounding the lesions and have lesions at different locations. However, previous studies with human subjects have reported similar results, [ 11 , 12 , 16 ] thus supporting the validity of our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, high reproducibility and accuracy in the phantom may not be in accordance with human subjects, which have heterogeneous background surrounding the lesions and have lesions at different locations. However, previous studies with human subjects have reported similar results, [ 11 , 12 , 16 ] thus supporting the validity of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Cosgrove et al [11] reported the excellent intraobserver reproducibility of the SWE of palpated breast masses in all diameter, areas, and perimeters and the good agreement of measured kPa (ICC: 0.94, 95% CI: 0.94-0.95; ICC: 0.87, 95% CI: 0.85-0.88). Hong et al [16] reported similar results on the inter-and intraobserver reproducibility of SWE (ICC: 0.879 and 0.803, retrospectively) for the mean value of measured kPa in patients with breast lesions.. Park et al [12] reported that the ICC of intraobserver reproducibility was 0.789 with SWE in malignant breast masses. In line with previous studies, the current study supports the excellent reproducibility of SWE in targets with various sizes and elasticity.…”
Section: Discussionmentioning
confidence: 73%
“…We included the mean of consecutive measurements in the statistical analysis to overcome this problem. Although there is no data on SMI, previous studies have shown that the reproducibility of the 2D‐SWE technique is high 29,30 . Finally, since a considerable part of our study population received neoadjuvant chemotherapy and postoperative results could not be achieved in a small group, statistical analysis was performed only Ki‐67 values of the core biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no data on SMI, previous studies have shown that the reproducibility of the 2D-SWE technique is high. 29,30 Finally, since a considerable part of our study population received neoadjuvant chemotherapy and postoperative results could not be achieved in a small group, statistical analysis was performed only Ki-67 values of the core biopsy specimens. The recommendation of the IKGW group to use Ki-67 values obtained from the core biopsy was considered, although both core biopsy and excision samples were suitable.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a large difference in the elasticity values of normal Achilles tendons between the study of Arda et al [3] and the study of Chen et al [7]. Although good intra-and inter-operator reproducibility of SWE has been proven for superficial tissues such as the breast [24], in a study of SWE applied to the supraspinatus muscle, Rosskopf et al [18] reported lower reliability in deep tissues and tissue close to the bone structure. Differences in measured and those without a tangent sign (negative tangent sign) (median, 83.50 kPa; IQR, 83.20 to 83.80 kPa; P=0.485).…”
mentioning
confidence: 95%